The Polemic of Ahad Hadith Use in Interpreting the Death of Prophet Isa According to Mahmud Syaltut and Siradjuddin Abbas - Karnedi, Rozian; Suryadi, Suryadi; Suryadilaga, Muahammad Alfatih (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2019)
This article aims to discuss some differences between Mahmud Shaltut and Siradjuddin Abbas in interpreting the verses about the death of prophet Isa. This paper also seeks to investigating of how they interpret, what methods they use, and what factors influence these differences. The results of the study reveal that Mahmud Shaltut interpretes the term of the tawaffa (Q.S Âli ´Imrân [3] verse 55) and tawaffaitanî (Q.S. al-Maidah [5] verse 117) in accordance with the original meaning of “death”. On the contrary, Siradjuddin Abbas exegetes the term of tawaffa by “grasp”. These differences are because Siradjuddin Abbas uses the method of tafsir bi al-riwayah and consideres them as hadith[s] sahih. On the contrary, Mahmud Shaltut uses the method of tafsir bi al-ra’yi and does not use such hadith[s]. As a figure of reformer in Egypt, the interpretation of Mahmud Shaltut is affected by Muhammad Abduh’s opinion who refuses the use of Ahad Hadith in belief/akidah discussion while Siradjuddin Abbas, as a traditional Islamic figure in Indonesia, attempts to counter Muhammad Abduh’s opinion because it contradicts to the understanding of ahl al-sunnah wa al-jamaah that he followed.